Inflammation and atherosclerosis - Grundtman, Cecilia; Wick, Georg (Springer Vienna, 2012)
It has been known for over 150 years that hallmarks of inflammation can be observed in the wall of atherosclerotic vessels. It was, however, not clear if this inflammation is the cause or the consequence of atherogenesis. More recently, it has become evident that inflammation mediated both by innate and adaptive immunity is instrumental even in the earliest stages of the development of atherosclerotic lesions, i.e., that it plays an important pathogenetic role. In this volume, international experts in the field discuss the pathogenetic, diagnostic, preventive and possible therapeutic relevance of inflammation in atherogenesis. This book is intended for researchers and physicians in the fields of vascular biology, immunology and atherosclerosis.